Seek and decode: Random access with physical‐layer network coding and multiuser detection*. Issue 5 (7th December 2016) - Cocco, Giuseppe; Pfletschinger, Stephan; Navarro, Monica
Abstract: We present a novel scheme for Slotted ALOHA random access systems that combines physical‐layer network coding (PLNC) with multiuser detection (MUD). The PLNC and MUD are applied jointly at the physical layer to be able to extract any linear combination of messages experiencing a collision within a slot. The set of combinations extracted from a whole frame is then processed by the receiver to recover the original packets. A simple precoding stage at the transmitting terminals allows the receiver to further decrease the packet loss rate. We present results for the decoding at the physical layer as well as several performance measures at frame level, namely, throughput, packet loss rate, and energy efficiency. The results we present are promising and suggest that a cross‐layer approach leveraging on the joint use of PLNC and MUD can significantly improve the performance of random access systems in the presence of slow fading. Abstract : We present a novel scheme for Slotted ALOHA random access systems that combines physical‐layer network coding with multiuser detection. The physical‐layer network coding and multiuser detection are applied jointly at the physical layer to extract any linear combination of messages experiencing a collision. The set of combinations extracted from a whole frame is then processed by the receiver to recover the original packets. A precoding stage at the transmitters allows the receiver to further decrease the packet loss rate.